Fostering sustainable development under the EU–Vietnam Investment Protection Agreement: a need for enhancing cooperation through support mechanisms - Dung Tran Viet; Huong Nguyen Thi Lan (TalTech Journal of European Studies)
The EU–Vietnam Investment Protection Agreement (EVIPA), signed by the parties in 2019, represents a significant shift from traditional investment treaties by integrating sustainable development objectives and explicitly recognizing the host state’s regulatory autonomy. The agreement also includes a number of provisions aimed at balancing investor protection with public policy goals. However, concerns persist regarding the clarity and effectiveness of these novel regulations for achieving this balance. The parties to the EVIPA have agreed to introduce a groundbreaking investment dispute settlement mechanism designed to enhance legal stability and clarity in the treaty’s interpretation and implementation. This study underscores the importance of prioritizing these mechanisms while addressing existing limitations in the regulatory framework, particularly concerning the right to regulate and exception clauses.